2016
DOI: 10.18321/ectj367
|View full text |Cite
|
Sign up to set email alerts
|

Catalysts for Alkylbenzene and Alkylpyridine Ammoxidation

Abstract: <p>An increase of effectivity of binary and ternary vanadium containing oxide catalysts can be achieved by a regulation of chemical and phase catalyst composition during their preparation. Activity and selectivity of V-Ti catalysts depend on the ratio of V<sub>2</sub>O<sub>5</sub> to VO<sub>2</sub> in the succession of substitutional solid solutions VO<sub>2</sub>- TiO<sub>2</sub>, as well as on the crystal modification of TiO<sub>2</su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Vanadium-zirconium oxide catalysts showed high selectivity in the process of oxidative ammonolysis of 3-picoline [12,13]. We have previously shown that the oxide vanadium-titanium-zirconium catalyst exhibits high activity and selectivity in the oxidative ammonolysis of 4-methylpyridine, making it possible to obtain 4-cyanopyridine with a yield of 90-95% at a temperature of 260-270 °C and minimum consumption of ammonia [13].…”
mentioning
confidence: 99%
“…Vanadium-zirconium oxide catalysts showed high selectivity in the process of oxidative ammonolysis of 3-picoline [12,13]. We have previously shown that the oxide vanadium-titanium-zirconium catalyst exhibits high activity and selectivity in the oxidative ammonolysis of 4-methylpyridine, making it possible to obtain 4-cyanopyridine with a yield of 90-95% at a temperature of 260-270 °C and minimum consumption of ammonia [13].…”
mentioning
confidence: 99%